Darfur diaries : stories of survival / stories of survival - Marlowe, Jen.; Bain, Aisha; Shapiro, Adam.; Rusesabagina, Paul, 1955-; Deng, Francis Mading, 1938- (New York : Nation Books, 2006)
"In November 2004 three independent filmmakers traveled to eastern Chad and crept across the border into Darfur. Improvising as they went, they spoke with dozens of Darfurians, learning about their history, hopes, fears, and the resilience and tragedy of their everyday lives"--Cover, P. [4].
Getting started -- Life as a refugee -- Crossing the border -- Destruction of Darfur -- The SLA -- Anka -- The Antonov plane and the wedding -- Dero -- Kariare camp -- Heading home -- Completing the film.
Keywords: Humanitarian assistance -- Sudan -- Darfur; Atrocities -- Sudan -- Darfur; Documentary films -- Production and direction; Darfur (Sudan); Sudan; Darfur